Friday

April 18, 2014

April 18, 2014

Posted by **AHKSIJ** on Wednesday, December 7, 2011 at 12:08pm.

- calculus -
**Steve**, Wednesday, December 7, 2011 at 1:35pmf = g(e^2x)

f' = 2e^2x g'

f'' = 4e^2xg' + 2e^2xg''

example:

g(x) = x sinx

f(x) = g(e^2x) = e^2x sin(e^2x)

g' = sinx + xcosx

g'' = cosx + cosx - xsinx

= 2cosx - xsinx

f' = 2e^2x sin(e^2x) + e^2xcos(e^2x)*2e^2x

= 2e^2x(sin(e^2x) + e^2x cos(e^2x))

Letting g(e^2x) = g(u)

f' = 2e^2x g'(u)

I have expanded out

4e^2xg'(u) + 2e^2xg''(u)

and it checks out. Have lots of blank paper!

**Related Questions**

calculus - f(x) = x^2 g(x) = e^2x h(x) = ln(2x) which function is increasing the...

calculus 2 - Suppose that you can calculate the derivative of a function using ...

calculus - Calculate f" for f(x)=g(e^(2x)), where g is a function defined for ...

calculus - Differentiate the function. g(x)= x^2(1-2x) g'(x)= i tried doing 2x(1...

Calculus Quiz Today - 1. find the values of s for which each function is ...

Calculus - Consider the function f(x)=2x+6x^(-1). For this function, there are ...

calculus help please - Consider the function f(x)=2x+9x^1.? For this function ...

calculus - Is this a correct answer, I'm trying to integrate the marginal ...

College Algebra - Here is the whole question... I have figured most of it out ...

Math - 2x^3 + 3x^2 + x + 1 dx --------------------- -2x + 1 [2x^3 + 3x^2 + x...